Your Brain Goes to Church: Neuroscience and Congregational Life - Sitze, Bob (Rowman & Littlefield Publishers, 2004)
The ever-provocative author and presenter Bob sitze explores the question: What does the human brain have to do with the beliefs, practices, and structures of congregations? Weaving together clear, accessible explanations about the workings of the human brain. Sitze shows how a congregation’s identity and behaviors are shaped by the work of individual members’ brains as well as "the collected brain" of the congregation. Study groups will enjoy the "Big Question" Sitze asks throughout the book, as well as the discussion questions and follow-up activities included at the end of each chapter.